The Climate Change-Temperature-Crime Hypothesis: Evidence from a Sample of 15 Large US Cities, 2002 to 2015 - Lynch, Michael J. (International journal of offender therapy and comparative criminology, 2022)
Drawing on prior studies, green criminologists have hypothesized that climate change will both raise the mean temperature and the level of crime. We call this the ?climate change-temperature-crime hypothesis? (?CC-T-C?). This hypothesis is an extension of research performed on temperature and crime at the individual level. Other research explores this relationship by testing for the relationship between seasonality and crime within a given period of time (i.e., within years). Climate change, however, produces small changes in temperature over long periods of time, and in this view, the effect of climate change on crime should be assessed across and not within years. In addition, prior CC-T-C studies sometimes employ large geographic aggregations (e.g., the entire whole United States), which masks the CC-T-C association that appears at lower levels of aggregation. Moreover, globally, crime has declined across nations since the early 1990s, during a period of rising mean global temperatures, suggesting that the CC-T-C hypothesis does not fit the general trends in temperature and crime over time. Addressing these issues, the present study assesses the CC-T-C relationship for a sample of 15 large (N?=?15) US cities over a 14-year period. Given the CC-T-C hypothesis parameters, we assessed this relationship using correlations between individual crime and temperature trends for each city. Crime trends were measured by both the number and rate of eight Uniform Crime Report (UCR) Part I crimes, so that for each city, there are 16 crime-temperature correlations. Using a liberal p value (p?=?.10), the temperature-crime correlations were rejected as insignificant in 220 of the 234 tests (94%). We discuss the Implications of this finding and suggest that rather than focusing on the temperature-crime relationship, green criminologists interested in the deleterious effects of climate change draw attention to its larger social, economic, environmental and ecological justice implications.